2022
DOI: 10.3389/fnmol.2022.887426
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Continuous Theta Burst Stimulation Can Regulate Sensitivity on Aβ Fibers: An Functional Near-Infrared Spectroscopy Study

Abstract: ObjectiveHigh-frequency repetitive transcranial magnetic stimulation (rTMS) induces analgesic effects in both experimental pain and clinical pain conditions. However, whether rTMS can modulate sensory and pain thresholds on sensory fibers is still unclear. Here, we compared the effects of three rTMS paradigms on sensory and pain thresholds conducted by different sensory fibers (Aβ, Aδ, and C fibers) with sham stimulation and investigate the potential brain activation using functional near-infrared spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Among these 14 studies, one of them was a doubleblinded randomized controlled trial (RCT) [24], while the rest of the studies were observational studies including cross-over trials, cohort studies, and some without controlled groups [22,23,[27][28][29][30][31][32][33][34][35][36][37]. All studies enrolled healthy adults.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these 14 studies, one of them was a doubleblinded randomized controlled trial (RCT) [24], while the rest of the studies were observational studies including cross-over trials, cohort studies, and some without controlled groups [22,23,[27][28][29][30][31][32][33][34][35][36][37]. All studies enrolled healthy adults.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…A previous review comprising nine such studies predominantly adopted a low-frequency inhibitory rTMS protocol [21]. In recent years, new studies featuring a larger number of participants, more rigorous experimental designs, and the incorporation of diverse rTMS protocols, including highfrequency facilitative protocols, have been conducted [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that prolonged continuous theta burst stimulation (pcTBS) modulates the sensitivity of Aβ fibers and pain thresholds in healthy adults. Single pcTBS placed on the left M1 increases the excitability of DLPFC and FPC, suggesting that the interaction between M1 and PFC may be a potential mechanism for the analgesic effects of HF-rTMS [ 146 ]. However, studies in patients with central post-stroke pain are needed to confirm the clinical effects of pcTBS.…”
Section: Overview Of Neuromodulation and Nibsmentioning
confidence: 99%
“…Amidst the rising prevalence of chronic pain and emerging consensus that transition to chronic pain is centrally regulated, there has been little clarity about the cellular and molecular mechanisms underlying the chronification, which is key to therapeutic targeting. Previous studies have shown that transcranial stimulation of PFC could relieve chronic pain 15,84,85 . Such studies, although established a causal connection, did not provide a long-term solution for pain management owing to the deleterious effects of broad non-specific cortex-wide stimulations.…”
Section: The L5 Et1 Neuron Subtype Might Regulate Chronic Pain Throug...mentioning
confidence: 99%
“…Increasing evidence indicates that disruption of this regulation is associated with the development of chronic pain, a rapidly increasing healthcare challenge that affects about 20% of the US population, exceeding cost burden of diabetes or heart disease 7,8 . Chronic pain has been associated with PFC hypoactivity, and transcranial stimulation of the PFC can induce pain relief [9][10][11][12][13][14][15] . Although projections from PFC to brainstem has been historically described in descending inhibition of pain 5,16,17 , the underlying molecular mechanism is poorly characterized.…”
Section: Introductionmentioning
confidence: 99%